6x+1=-0.4x-2

Simple and best practice solution for 6x+1=-0.4x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+1=-0.4x-2 equation:


Simplifying
6x + 1 = -0.4x + -2

Reorder the terms:
1 + 6x = -0.4x + -2

Reorder the terms:
1 + 6x = -2 + -0.4x

Solving
1 + 6x = -2 + -0.4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.4x' to each side of the equation.
1 + 6x + 0.4x = -2 + -0.4x + 0.4x

Combine like terms: 6x + 0.4x = 6.4x
1 + 6.4x = -2 + -0.4x + 0.4x

Combine like terms: -0.4x + 0.4x = 0.0
1 + 6.4x = -2 + 0.0
1 + 6.4x = -2

Add '-1' to each side of the equation.
1 + -1 + 6.4x = -2 + -1

Combine like terms: 1 + -1 = 0
0 + 6.4x = -2 + -1
6.4x = -2 + -1

Combine like terms: -2 + -1 = -3
6.4x = -3

Divide each side by '6.4'.
x = -0.46875

Simplifying
x = -0.46875

See similar equations:

| (x+y)(x+2y)= | | 3(2-x)-2(2x+1)=3 | | 6x+1=0.4x+2 | | 2-3(4x)=5(2-x)+4x | | -4x-35=3x | | 4k-(2k-5)=0 | | 8y=15y-13 | | 5(x-2)+x=6(8+3)-4x | | C+(c+2)+(c+4)=-57 | | 1+2log(x+1)=log(2x+1)+log(5x+8) | | 3x-5-4x=10+65-3x | | 1+2lg(x+1)=lg(2x+1)+lg(5x+8) | | y^2-11y+36=0 | | 2x+1+2(2-x)=x | | 12=5x+3y | | 5-3(a-12)+a= | | 128=6x*8 | | F(6)=3x-14 | | 28+12x=8x+4 | | 8m-3=13+3+8m+7 | | 2x+40=7x | | 2x-5=1+2x-6 | | 3x+2(x+6)=9x+4 | | x^2+3x=128 | | 5t-3t+18t-2+t=12 | | -x+14y=-19 | | 5-7=6 | | 17=221/x | | -8/3*(-7/9) | | X^2+3x-10=3 | | -4(8+6x)=32+8x | | 4t+9=-7m+18 |

Equations solver categories